Lung Matrix Metalloproteinase Activation following Partial Hepatic Ischemia/Reperfusion Injury in Rats - Giuseppina Palladini; Andrea Ferrigno; Vittoria Rizzo; Eleonora Tarantola; Vittorio Bertone; Isabel Freitas; Stefano Perlini; Plinio Richelmi; Mariapia Vairetti (The Scientific World Journal)
Purpose. Warm hepatic ischemia-reperfusion (I/R) injury can lead to multiorgan dysfunction. The aim of the present study was to investigate whether acute liver I/R does affect the function and/or structure of remote organs such as lung, kidney, and heart via modulation of extracellular matrix remodelling. Methods. Male Sprague-Dawley rats were subjected to 30 min partial hepatic ischemia by clamping the hepatic artery and the portal vein. After a 60 min reperfusion, liver, lung, kidney, and heart biopsies and blood samples were collected. Serum hepatic enzymes, creatinine, urea, Troponin I and TNF-alpha, and tissue matrix metalloproteinases (MMP-2, MMP-9), myeloperoxidase (MPO), malondialdehyde (MDA), and morphology were monitored. Results. Serum levels of hepatic enzymes and TNF-alpha were concomitantly increased during hepatic I/R. An increase in hepatic MMP-2 and MMP-9 activities was substantiated by tissue morphology alterations. Notably, acute hepatic I/R affect the lung inasmuch as MMP-9 activity and MPO levels were increased. No difference in MMPs and MPO was observed in kidney and heart. Conclusions. Although the underlying mechanism needs further investigation, this is the first study in which the MMP activation in a distant organ is reported; this event is probably TNF-alpha-mediated and the lung appears as the first remote organ to be involved in hepatic I/R injury.